KEPASTIAN HUKUM TERHADAP PEMEGANG HAK MILIK DALAM PENERBITAN SERTIPIKAT TANAH GANDA PADA SATU BIDANG TANAH - Lulu Fitriani; Muhammad Sofyan Pulungan; Isyana Wisnuwardhani Sadjarwo (LPPM Universitas Ekasakti Padang, 2021)
Certificate of land ownership regulated in the Undang-Undang Pokok Agraria (“UUPA”) is an ownership proof of the land right where it becomes powerful evidence. The increasement of necessity of a land is not followed by the increasement of the availability of land that can be utilized by the society, which causes many disputes related to the ownership or land right. One of many problems that arises is double certificate on a land. Double certificate on a land causing risks on the owner of land right where such phenomena caused by the maladministration to criminal action. Badan Pertanahan Nasional (“BPN”) as an institution established by the Government that holds the sole authority in national land should be responsible in the matters related to the land dispute, especially double certificate. Beside that, there is a necessity on the legal protection to be provided by the State for the owner of land right to protect the rights of the land owner. The research performed using juridical normative with legislation approach and conseptual approach. Research result will be written in the form of explanatory-analysis where the writer explains the case in the case of lawsuit and the theories related with the problem, then analyzes the consistency between the problem and the applicable laws and regulations or theories. Keywords: Land Dispute, Double Certificate, Legal Protection.